Tingkat Pengetahuan Perkembangan Teknologi Indonesia pada Mahasiswa di Kota Medan - Hafizh Fahriza; Muhammad Irwan Padli Nasution (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
This study aims to evaluate the level of knowledge about technological developments among students in Medan City. The survey method was used to collect data from a representative sample of students from various universities in the region. This research analyzes their understanding of the latest technological trends, use of technology in everyday life, as well as awareness of emerging technological innovations. The findings of this study can provide valuable insights for educators, researchers, and policy makers in increasing technological understanding among the younger generation, which is key to preparing them to face the growing demands of the future in the technological realm.